EFEK MEDIASI WORK-FAMILY CONFLICT TERHADAP STRES KERJA PADA IBU BEKERJA DI RUMAH SELAMA PANDEMI COVID-19 (Universitas Teknologi Muhammadiyah Jakarta (UTM Jakarta), 2021)
Teleworking mothers in Indonesia have been stressed due to work-family conflicts during the Covid-19 pandemic. Whilst most scholars likely have been studied work-family conflict and work stress partially, this study proposed a more comprehensive structural model of causality by analyzing the effect of spousal and organizational support toward work stress on teleworking mothers during the Covid-19 pandemic through the mediation of work-family conflict. This study used a purposive sampling technique in collecting 57 respondents that appropriated to the criteria of study such as teleworking mother during the Covid-19 pandemic, live in Jabodetabek, and possess one child or more. This study used path analysis with two models of direct and indirect. The results indicated that spousal support and organizational support directly and negatively affected work-family conflict, but did not directly affect work stress. Work-family conflict directly and positively affected work stress, while spousal and organizational support indirectly and negatively affected work stress through the mediation of work-family conflict. Therefore, teleworking mothers who have been stressed during the pandemic due to work-family conflicts are recommended to improve their spousal dan organizational support in reducing their level of work stress.